Exfoliated MoS2 with porous graphene nanosheets for enhanced electrochemical hydrogen evolution - Liu, Y.; Liu, J.; Li, Z.; Fan, X.; Li, Y.; Zhang, F.; Zhang, G.; Peng, W.; Wang, Shaobin (Elsevier Ltd, 2018)
Porous graphene (P-rGO) was synthesized from graphene oxide (GO) via a one-pot calcination method with CO2 as an activation agent at 800 °C. Due to the special porous structure, the surface area of P-rGO can be increased to ∼759 m2/g. The P-rGO was then used as a support to incorporate with chemical exfoliated molybdenum disulfide (MoS2) for the fabrication of MoS2/P-rGO composite. Compared to bulk MoS2, the exfoliated MoS2 is in the 1T phase with a metallic property and smaller charge transfer resistance, thus has a better activity in electrochemical hydrogen evolution reaction (HER). The HER activity of 1T MoS2 could be further increased after the combination with P-rGO. The overpotential of 1T MoS2/P-rGO was only ∼130 mV vs. RHE, and the corresponding Tafel slope was ∼75 mV Dec−1. The special porous structure and good electric conductivity of P-rGO decrease the charge transfer resistance of the composite without sheltering too many active sites of MoS2, thus leading to the enhanced HER activity. As an efficient noble metal free HER catalyst, the 1T MoS2/P-rGO has great potential for large-scale hydrogen production.